Case Report: Pseudo-wide QRS complex tachycardia in an infant with complex congenital heart disease - Li, Hualian; Cong, Jingjing; Yu, Tingting; You, Zhongmin; Wen, Jie; Li, Heng (Frontiers in Pediatrics, 2026)
The initial electrocardiogram (ECG) of a 5-month-old infant with complex congenital heart disease (pulmonary valvular stenosis, ventricular septal defects, and patent ductus arteriosus) revealed a regular wide QRS tachycardia at 169 bpm, initially suggestive of ventricular tachycardia (VT) or supraventricular tachycardia (SVT) with aberrant conduction. However, a subsequent ECG obtained during spontaneous heart rate deceleration to 143 bpm showed narrow QRS complexes with discernible sinus P waves and a markedly prolonged PR interval (300 ms). These findings establish the diagnosis of sinus rhythm with biatrial enlargement and first-degree atrioventricular (AV) block. Comparative analysis of these ECGs revealed that the initial tracing did not represent a true wide QRS complex but rather a “pseudo-wide QRS complex” tachycardia. This phenomenon occurs when profound PR prolongation results in concealed sinus P waves overlapping the terminal portion of the preceding QRS complex, thereby mimicking a wide QRS complex. The significant PR interval prolongation, reflecting first-degree AV block, is likely attributable to underlying anatomical abnormalities leading to atrial enlargement and consequent impaired AV nodal conduction. This case report highlights the critical importance of meticulously identifying concealed sinus P waves within wide QRS rhythms to prevent misdiagnosis and inappropriate interventions.